Fullerenes - Ehrenreich, Henry; Spaepen, Frans (Solid state physics : advances in research and applications, 1994)
Fullerenes or"buckyballs, "a new carbon-based family of materials, have fascinated the scientific community for the past few years. These materials are likely to find applications ranging from lubricants to batteries to biological magic bullets, which will be of great importance in the science and technology of the next century. This carefully edited volume, the first to include Frans Spaepen as co-editor, summarizes our present understanding in a series of didacticarticles, which take the reader from the fundamentals to the present cutting-edge research. A general overview is followed by chapters devoted to synthesis and characterization of fullerenes and their derivatives, the novel structural properties of buckyballs, tubes, and buckyonions, a theoretical and experimental view of electrons and phonons, and finally to the fascinating superconducting properties of these materials. Key Features * Presents systematic overview of entire field * Discusses synthesis, characterization, structure, and superconducting properties * Specially edited volume of the distinguished Solid State Physics Series * Includes applications from many fields